2018
DOI: 10.7869/djo.394
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fundoscopic Findings in HIV Positive Patients in Relation to HAART and CD4 Count

Abstract: Aim: To evaluate the fundus findings in patients with HIV in correlation to highly active antiretroviral therapy (HAART) and CD4 count. Materials and Methods: It was a hospital based observational study. It was conducted from December 2014 to September 2016 in the Ophthalmology Department, Bharati Hospital, Sangli. A total of 195 registered HIV patients on HAART were selected for the study. Informed written consent of the subjects to participate in the study was taken. Patients of both sexes of any age group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…19 However, the prevalence of cataract in our study population was higher than that reported amongst PLHIV elsewhere in India. [20][21][22] This might be owing to the use of slit lamp and dilated fundus examination conducted in all individuals who did not improve to 6/6, where even small lenticular opacities would have been detected. A report on cataract risk in HIV-infected individuals stated that compartmentalized residual intraocular HIV viremia, despite ART, and secondary chronic inflammation could be factors promoting cataract in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, the prevalence of cataract in our study population was higher than that reported amongst PLHIV elsewhere in India. [20][21][22] This might be owing to the use of slit lamp and dilated fundus examination conducted in all individuals who did not improve to 6/6, where even small lenticular opacities would have been detected. A report on cataract risk in HIV-infected individuals stated that compartmentalized residual intraocular HIV viremia, despite ART, and secondary chronic inflammation could be factors promoting cataract in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular manifestation may be the primary presentation of HIV. The eye is an organ with wide spectrum of HIV-related manifestation, and the disease can present with adnexal, anterior segment, posterior segment, orbital, and neuro-ophthalmic manifestation [5].…”
Section: Methodsmentioning
confidence: 99%